A Health Education Intervention to Improve Diabetic Foot Ulcer Prevention: Effects on Knowledge, Self-Efficacy, Social Support, and Foot Care Practices - Rita Sari; Janu Purwono (Journal of Health Education, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a major global health concern that disproportionately affects low- and middle-income countries. Health education is a fundamental component of diabetes management, as it enhances health literacy by improving patients' knowledge, self-efficacy, foot care practices, and social support. This study aimed to evaluate the effectiveness of a health education intervention in preventing diabetic foot ulcers (DFUs). Methods: This quasi-experimental study employed a one-group pretest–posttest design. The study was conducted over a nine-month period among patients with T2DM in Pringsewu Regency. Of the 350 patients with T2DM, 107 participants were recruited using purposive sampling. Data were analyzed using the chi-square test. Results: The health education intervention significantly improved participants' knowledge, self-efficacy, foot care practices, and perceived social support. Furthermore, the intervention demonstrated a significant effect in preventing DFUs, with all outcome measures showing statistical significance (p < 0.05). Conclusion: Health education effectively enhances knowledge, self-efficacy, foot care practices, and social support, thereby contributing to the prevention of DFUs among patients with type 2 diabetes mellitus.